Grieving as an Internal Factor of Nurse-Patient Interaction in a Dialysis Unit - Ika Yuni Widyawati; Nursalam Nursalam; Kusnanto Kusnanto; Rachmat Hargono; Pei-Lun Hsieh (Universitas Airlangga, 2018)
Introduction: The quality of the nurse-patient interaction is one factor that affects the patient adherence, but a study that provides an overview of factors in the nurse-patient interaction in improving or maintaining dialysis patient adherence has not been found. The aim of this study was to provide an overview of the various factors involved in the interaction process between nurses and patients undergoing dialysis in relation to their adherence to fluid and dietary restrictions.Methods: A qualitative research design with an interpretive phenomenology approach was used in this study. The researcher intends to interpret the findings of the research, in this case the activity of the dialysis patients, in order to get a picture of the various factors involved in the process of interaction between nurse and dialysis patient. The unit of analysis used in this study was the disclosure or exposure of the internal factors of the nurse-patient interaction process, especially in relation to fluid and dietary restrictions. There were 15 participants who were selected based on the inclusion criteria. In-depth interviews, with field notes, were used in this study as the data collection method.Results: The analysis of the theme based on the goal of the research includes grieving, needs and values/morals, but in this article, the researchers only describe one theme - grieving.Conclusion: This result provides an overview of the findings on nurse-patient interaction factors that can serve as baseline data for the development of nursing care, both in nursing assessments and interventions aimed at improving dietary adherence and the fluid restriction of dialysis patients.